2013
DOI: 10.1182/blood-2013-04-496950
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 infection of hematopoietic progenitor cells in vivo in humanized mice

Abstract: Key Points Some CD34+CD38+ intermediate hematopoietic progenitor cells express HIV-1 entry receptors and are susceptible to direct infection by HIV. Blood progenitors from HIV-exposed, humanized BLT mice show impaired hematopoietic potential and give rise to progeny that harbor provirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 37 publications
3
36
1
Order By: Relevance
“…Humanized mouse models have been used widely to investigate the mechanisms of HIV-1 immunopathogenesis, including functionally defining the role of regulatory T cells (41), pDCs (30), and other cells (29) in acute and chronic HIV-1 infection. In the present study, we found that human ILC3 subsets were functionally developed in all lymphoid organs in NRG-hu mice and preferentially resided in the spleen and mLN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humanized mouse models have been used widely to investigate the mechanisms of HIV-1 immunopathogenesis, including functionally defining the role of regulatory T cells (41), pDCs (30), and other cells (29) in acute and chronic HIV-1 infection. In the present study, we found that human ILC3 subsets were functionally developed in all lymphoid organs in NRG-hu mice and preferentially resided in the spleen and mLN.…”
Section: Discussionmentioning
confidence: 99%
“…We thus took advantage of the well-developed humanized mouse model to investigate the function and role of ILC3 in HIV-1 pathogenesis (28)(29)(30)(31) Figure 2). We found that ILC3s were efficiently developed in all lymphoid organs of humanized mice including spleen, mesenteric lymph node (mLN), peripheral lymph node (pLN), BM, and peripheral blood lymphocytes (PBL) ( Figure 2A).…”
Section: Introductionmentioning
confidence: 99%
“…Because some analyses of plasma virus found that certain identical sequences predominate in circulation over multiple time points, it was proposed that latently-infected stem cells, with the capacity for self-renewal, contributed clonal virus upon intermittent activation [3]. Indeed, a number of studies have provided evidence that HIV can infect CD34 + bone marrow progenitors [7–9,3436]. A study of HIV-infected people in Africa revealed that HIV-1 subtype C could infect HSPCs in vitro and in vivo .…”
Section: Defining Latent Reservoirsmentioning
confidence: 99%
“…In addition, lentiviral-mediated gene delivery of the HSV-tk/GCV suicide system has been used in HIV-infected cells 32 and to control graft-versus-host disease in a phase I/II clinical trial in patients with leukemia 74 . Recently, it has been shown that HIV can infect cells of the hematopoietic lineage in vivo, 75 and novel lentiviral vectors targeting CD34 + hematopoietic progenitor cells have been described 76 . Bone marrow gene therapy is an attractive technology for HIV antiviral therapies (reviewed by Herrera-Carrillo et al 17 …”
Section: Discussionmentioning
confidence: 99%